An Examination of How Problem-Based Learning Influences The Mathematical Literacy Capabilities of Middle School Students, Analyzed Through The Lens of Learning Preferences - Hasmawati Hasmawati; Sukmawati Sukmawati; Sitti Fithriani Shaleh (Universitas Wiralodra, 2026)
Mathematical literacy is an essential competency that enables students to apply mathematical knowledge and reasoning to solve problems encountered in everyday life. However, students' mathematical literacy skills remain relatively low, indicating the need for instructional approaches that promote meaningful learning. This study aimed to examine the effectiveness of the Problem Based Learning (PBL) model in improving students' mathematical literacy skills, to determine the effect of learning styles on mathematical literacy skills, and to investigate the interaction between the PBL model and learning styles. This study employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The participants were seventh-grade students of SMPN 1 Bontolempangan selected through cluster random sampling. The experimental group consisted of 34 students who were taught using the Problem Based Learning (PBL) model, while the control group consisted of 33 students who received conventional instruction. Data were analyzed using a two-way analysis of variance (Two-Way ANOVA) at a significance level of 0.05. The findings revealed that the Problem Based Learning (PBL) model had a significant positive effect on students' mathematical literacy skills (p < 0.001). In contrast, learning styles did not have a statistically significant effect on students' mathematical literacy skills (p = 0.649). Furthermore, no significant interaction was found between the learning model and learning styles in influencing students' mathematical literacy skills (p = 0.308). In conclusion, the Problem Based Learning (PBL) model is more effective than conventional instruction in improving students' mathematical literacy skills. However, students' learning styles do not significantly influence mathematical literacy achievement, nor do they moderate the effectiveness of the learning model.